A battery

CN122907703APending Publication Date: 2026-10-13ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610954604.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]本申请的首要目的是提供一种电池,以解决含高硅负极的电池因设置胶纸而导致电解液浸润性不足、同时难以兼顾胶纸对正极片与负极片之间分层的约束需求的问题

Benefits of technology

本申请提供的电池,通过在电极组件的侧面包覆带有通孔的胶纸,并进一步限定单位面积内通孔面积s与负极活性层中硅元素质量含量a满足:0.05≤a×s≤0.6,可在负极硅含量较高导致电池膨胀幅度增大的情况下,使胶纸具有足够的结构强度,防止其在反复膨胀收缩中断裂失效,从而持续发挥其隔离空箔区与PP层、抑制正负极分层的约束作用;同时兼顾电解液浸润性能,避免因通孔面积过小而导致的浸润不良。在此基础上,本申请进一步引入低黏度的氟代乙酸乙酯,其质量分数控制在4%~60%,能够显著降低电解液的流动阻力,使其更容易通过通孔渗透至极片界面,补偿因通孔面积受限而可能产生的浸润损失。由此,既保障了高硅负极体系下胶纸对极片分层的有效抑制,又有助于电解液充分浸润电芯内部,降低了局部析锂和容量衰减的风险。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907703A_ABST
    Figure CN122907703A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of secondary batteries, and discloses a battery, which comprises an electrode assembly and an electrolyte, the electrode assembly comprises a positive electrode sheet, a negative electrode sheet and a separator, the negative electrode sheet contains a silicon-based material, the mass content of silicon in the negative electrode active layer is a%, the electrode assembly further comprises adhesive paper, the adhesive paper extends from a first surface of the electrode assembly to a second surface, a through hole is arranged in the part of the adhesive paper corresponding to the thickness direction of the electrode assembly, the total area of the through hole in the unit square centimeter range of the adhesive paper is s mm 2 , 0.05 <= a * s <= 0.6 is met, and the electrolyte comprises fluoroethyl acetate with a mass content of 4% to 60%. According to the application, the relationship between the total area of the through hole and the silicon content is limited, the electrolyte is promoted to infiltrate while the adhesive paper is guaranteed to constrain the expansion of the electrode sheet, the risk of lithium precipitation is reduced, the aging time is shortened, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery technology, and specifically to a battery. Background Technology

[0002] Lithium-ion batteries boast advantages such as high energy density and long cycle life, making them widely used in portable electronic devices, electric vehicles, and other fields. Currently, lithium-ion batteries primarily employ two structures: wound and stacked. Both types of cells typically have a single-sided area. In this area, the foil is coated with active material only on one side, resulting in uneven stress on both sides. During charging and discharging, the edge of the foil in this single-sided area is prone to outward curling, repeatedly compressing the polypropylene (PP) layer of the aluminum-plastic film, leading to PP layer wear, aluminum layer corrosion, and electrolyte leakage. On the other hand, to further improve battery energy density, silicon-based materials are often incorporated into the negative electrode. However, when the silicon content in the negative electrode is high, the significant volume expansion of the silicon material exacerbates the spatial changes of the electrode, making the unbalanced stress on the single-sided area more prominent. This can easily lead to delamination between the positive electrode and the adjacent negative electrode, causing a rapid decrease in battery capacity and a significant shortening of cycle life.

[0003] To address the aforementioned issues, existing solutions typically involve wrapping adhesive tape around the perimeter of the stacked cells (or the corresponding sections of the wound cells). This tape isolates the empty foil area from direct contact with the PP layer, preventing the PP layer from being worn down by repeated friction. It also provides spatial constraint, suppressing delamination between the positive and negative electrodes, particularly effective in silicon anode systems. However, the introduction of this adhesive tape introduces new problems: the tape-covered area physically blocks the electrolyte's penetration path into the cell, significantly reducing the effective wetting area. This leads to poor wetting between the positive and negative electrodes, inducing lithium plating and further accelerating battery capacity decay. Summary of the Invention

[0004] The primary objective of this application is to provide a battery that addresses the problems of insufficient electrolyte wettability in batteries with high-silicon anodes due to the use of adhesive tape, while also making it difficult to meet the constraint requirements of the adhesive tape on the delamination between the positive and negative electrode sheets.

[0005] Another objective of this application is to provide a battery with a long cycle life and high manufacturing efficiency.

[0006] The objective of this application is achieved through the following technical solution: According to an embodiment of this application, a battery is provided, including an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a separator, and a negative electrode stacked together, and the electrode assembly includes a first surface and a second surface disposed opposite to each other along its thickness direction. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the surface of the negative electrode current collector. The negative electrode active layer includes a silicon-based material, and the mass content of silicon element is a% based on the total mass of the negative electrode active layer. The electrode assembly further includes adhesive tape extending from the first surface to the second surface. The adhesive tape has through holes in a portion corresponding to the thickness direction of the electrode assembly. Within a unit square centimeter of the adhesive tape, the total area of ​​the through holes is 5 mm. 2 The condition is satisfied that: 0.05 ≤ a × s ≤ 0.6; The electrolyte includes ethyl fluoroacetate, and the mass content of ethyl fluoroacetate is f% based on the total mass of the electrolyte, satisfying: 4≤f≤60%.

[0007] Compared with the prior art, the technical solution of this application has the following advantages: The battery provided in this application, by covering the side of the electrode assembly with adhesive paper containing through holes, and further limiting the through hole area *s* per unit area to satisfy the following condition with the silicon content *a* in the negative electrode active layer: 0.05 ≤ *a* × *s* ≤ 0.6, ensures that the adhesive paper has sufficient structural strength to prevent breakage and failure during repeated expansion and contraction, even when the battery expansion is large due to the high silicon content in the negative electrode. This allows it to continuously perform its function of isolating the empty foil area from the PP layer and suppressing the delamination of the positive and negative electrodes. Simultaneously, it considers electrolyte wetting performance, avoiding poor wetting caused by excessively small through hole area. Furthermore, this application introduces low-viscosity ethyl fluorocarbonate, with its mass fraction controlled at 4%~60%, which significantly reduces the flow resistance of the electrolyte, making it easier for it to penetrate through the through holes to the electrode interface, compensating for potential wetting losses due to the limited through hole area. Therefore, it not only ensures the effective suppression of electrode delamination by the adhesive paper in the high-silicon negative electrode system, but also helps the electrolyte to fully wet the inside of the cell, reducing the risk of local lithium plating and capacity decay. Attached Figure Description

[0008] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0009] Figure 1 This is one of the structural schematic diagrams of an electrode assembly according to an embodiment of the present invention.

[0010] Figure 2 This is a schematic diagram of the adhesive tape structure according to an embodiment of the present invention.

[0011] Figure 3 This is a second schematic diagram of the structure of an electrode assembly according to an embodiment of the present invention.

[0012] Figure 4This is a scanning electron microscope image of a silicon-carbon material according to an embodiment of the present invention.

[0013] Explanation of reference numerals in the attached figures: 1. Electrode assembly; 11. First side; 12. Second side; 2. Adhesive tape; 21. First zone; 22. Second zone; 23. Third zone; 3. Through hole. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0015] In related technologies, to suppress delamination between electrodes caused by negative electrode expansion, and to address the leakage problem caused by the extrusion of the aluminum-plastic film polypropylene layer (PP layer) at the edge of the electrode on one side of the battery, a common approach is to wrap adhesive paper around the perimeter of the stacked cell or around the top and bottom of the wound cell. This approach provides spatial constraint on the electrodes and reduces direct contact between the edge of the electrode on one side and the polypropylene layer to some extent, thereby improving the cycle life and reliability of the battery.

[0016] However, when adhesive tape is applied to the sides and / or top and bottom of the battery cell, it forms a physical barrier around the cell. During electrolyte injection, the electrolyte mainly relies on the areas around the cell edges not covered by the tape to gradually penetrate inwards. Due to the obstruction effect of the tape, the wetting path of the electrolyte increases, while the wetting area decreases, making it difficult for the cell interior, especially the central region, to achieve sufficient wetting within a normal time. Insufficiently wetting results in the inability to form a good ion transport interface between the positive and negative electrodes, thereby inducing lithium plating and accelerating battery capacity decay. Furthermore, this problem becomes more pronounced with increasing silicon content in the negative electrode, as high-silicon negative electrodes are more sensitive to electrolyte consumption and demand.

[0017] To address the aforementioned problem of poor wetting, a direct approach is to create through-holes in the adhesive tape to provide additional channels for electrolyte penetration. However, this study found that while creating through-holes can improve wettability to some extent, the presence of these holes inevitably reduces the effective cross-sectional area of ​​the adhesive tape, thereby weakening its structural strength and maximum load-bearing capacity. Furthermore, for anodes with high silicon content, the volume expansion during charge and discharge is more pronounced, placing higher demands on the binding strength of the adhesive tape. The need to improve wettability and maintain adhesive tape strength present a contradiction; balancing these two aspects has become a critical issue hindering the performance improvement of silicon-containing anode batteries.

[0018] To address the aforementioned problems in related technologies, an embodiment of this application provides a battery including an electrode assembly 1 and an electrolyte. The electrode assembly 1 includes a positive electrode, a separator, and a negative electrode stacked together. The positive electrode, negative electrode, and separator can be assembled in a stacked manner to form the electrode assembly 1, or they can be assembled in a wound manner. The electrode assembly 1 includes a first surface 11 and a second surface 12 disposed opposite to each other along its thickness direction.

[0019] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector. The negative electrode current collector may be copper foil. The negative electrode active layer includes a negative electrode active material, a conductive agent, and a binder. The negative electrode active layer includes a silicon-based material. The silicon-based material may include at least one of silicon-carbon materials and silicon-oxygen materials. Based on the total mass of the negative electrode active layer, the mass content of silicon element is a%.

[0020] The electrode assembly 1 also includes adhesive tape 2. Adhesive tape 2 extends from the first surface 11 to the second surface 12 of the electrode assembly 1. That is, adhesive tape 2 simultaneously covers two large surfaces of the electrode assembly 1 that are opposite each other along the thickness direction, as well as the side surface connecting these two large surfaces. The portion of adhesive tape 2 corresponding to the thickness direction of the electrode assembly 1 has through holes 3. The through holes 3 penetrate the thickness direction of the adhesive tape 2. The shape of the through holes 3 can be circular, elliptical, rectangular, polygonal, or irregular, preferably circular or hexagonal. The through holes 3 can be formed by mechanical stamping, laser drilling, or ion etching. Within a unit square centimeter of adhesive tape 2, the total area of ​​the through holes 3 is s mm. 2 The total area s of the through holes 3 reflects the area of ​​the openings per unit area of ​​the adhesive tape 2. The larger this value is, the more channels the electrolyte can pass through the through holes 3, but the structural strength of the adhesive tape 2 will decrease accordingly.

[0021] The total area *s* of the through-hole 3 and the mass content *a* of silicon in the negative electrode sheet satisfy the condition: 0.05 ≤ *a* × *s* ≤ 0.6. When the value of *a* × *s* is less than 0.05, it means that the total area of ​​the through-hole 3 per unit area is too small relative to the silicon content. In this case, regardless of the silicon content, the through-hole 3 cannot provide sufficient electrolyte penetration channels, and the improvement effect on electrolyte wettability is not significant. Especially when the silicon content is high, although the strength requirement of the adhesive tape 2 is higher, the excessively small total area of ​​the through-hole 3 makes it even more difficult for the electrolyte to wet the interior of the high-silicon negative electrode, and the risk of lithium plating actually increases.

[0022] When the value of a×s is greater than 0.6, it means that the total area of ​​the vias 3 per unit area is too large relative to the silicon content, which excessively weakens the structural strength and maximum load-bearing capacity of the adhesive tape 2, making it difficult to effectively restrain the expansion of the negative electrode during charging and discharging. Specifically, when the silicon content is high, the negative electrode expansion is more severe, and the excessively large total area of ​​the vias 3 leads to insufficient strength of the adhesive tape 2, failing to effectively suppress electrode delamination. When the silicon content is low, although the negative electrode expansion is smaller, the excessively large total area of ​​the vias 3 still causes unnecessary loss of strength in the adhesive tape 2, and too many vias 3 may weaken the protective effect of the adhesive tape 2 on the electrode edges.

[0023] Therefore, by controlling a×s within the range of 0.05 to 0.6, the electrolyte transport capacity of the adhesive tape 2 and the structural strength of the adhesive tape 2 can be adapted to a balance based on the silicon content. For example, a×s can be 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, or values ​​within any two of the above ranges.

[0024] It should be noted that the value of a×s is obtained by multiplying the measured a% (in percentage terms, for example, 10 when a=10) by the measured total area s of the through holes within a unit square centimeter (in square millimeters).

[0025] The electrolyte comprises ethyl fluoroacetate. The ethyl fluoroacetate includes ethyl difluoroacetate; the ethyl difluoroacetate includes at least one of 2,2-difluoroethyl acetate and ethyl 2,2-difluoroacetate; preferably, the ethyl difluoroacetate includes 2,2-difluoroethyl acetate.

[0026] Ethyl fluoroethyl acetate has a low viscosity, and its addition to the electrolyte can reduce the overall viscosity of the electrolyte system. The lower viscosity electrolyte has better flowability, allowing it to diffuse more quickly along the surfaces of the positive and negative electrodes and the pores of the separator during the injection process. It also more easily enters the electrode assembly 1 through the tiny through-holes 3 on the adhesive tape 2, and has a smaller wetting angle on the electrode surface, enabling it to spread more fully on the positive and negative electrode surfaces and form a good solid-liquid interface. Based on the total mass of the electrolyte, the mass content of ethyl fluoroethyl acetate is f%, satisfying 4 ≤ f ≤ 60%.

[0027] When the mass content of ethyl fluoroacetate is less than 4%, the reduction in electrolyte viscosity is limited, and the electrolyte has difficulty passing smoothly through the micropores 3 on the adhesive tape 2, resulting in little improvement in wettability. When the mass content of ethyl fluoroacetate is higher than 60%, the excessively high ethyl fluoroacetate content may cause the overall viscosity of the electrolyte to increase again, which is detrimental to the wetting of the electrode surface.

[0028] Therefore, by controlling the mass content of ethyl fluoroacetate within the range of 4% to 60%, good ionic conductivity can be maintained while reducing electrolyte viscosity. The through-holes 3 on the adhesive tape 2, combined with the low-viscosity electrolyte, help shorten the wetting time and aging process cycle, reduce the risk of lithium plating due to localized electrolyte deficiency, and delay battery capacity decay.

[0029] For example, f% can be 4%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, etc., or a value within the range of any two of the above values.

[0030] It should be noted that the mass content of ethyl fluoroacetate can be determined by conventional methods in the art, such as gas chromatography (GC), gas chromatography-mass spectrometry (GCMS), or liquid chromatography (LC).

[0031] The battery provided in this application significantly improves electrolyte wetting efficiency while ensuring the binding ability of the adhesive tape 2 on the electrode sheet by leveraging the synergistic effect of the through holes 3 in the adhesive tape 2, the quantitative relationship between the total area of ​​the through holes 3 and the silicon content, and the low viscosity of ethyl fluoroacetate. Specifically, the through holes 3 on the adhesive tape 2 provide a direct channel for the electrolyte to enter the electrode assembly 1, while the ethyl fluoroacetate reduces the electrolyte viscosity, making it easier for the electrolyte to pass through the micro-through holes 3 and spread fully on the electrode surface. The combination of these two factors helps reduce the risk of lithium plating caused by localized electrolyte deficiency. Furthermore, by limiting the electrolyte transport capacity of the adhesive tape 2 to 0.05 ≤ a × s ≤ 0.6, its structural strength is adapted to the silicon content, which helps to ensure the strength of the adhesive tape 2 to restrain electrode expansion while promoting sufficient wetting of the electrolyte into the electrode assembly 1, thereby reducing the risk of lithium plating and improving the cycle stability of the battery.

[0032] The mass content of silicon in the negative electrode active layer can be determined by the following method: After discharging the battery to 0% SOC, disassemble and remove the negative electrode sheet. Soak it in DMC solvent for 12 hours, then rinse it with DMC solvent to remove the lithium salt adhering to the negative electrode sheet. After drying, treat the negative electrode sheet at 400℃ in an inert atmosphere for 2 hours (e.g., in a tube furnace under nitrogen or argon atmosphere). The negative electrode active layer can then be peeled off from the negative electrode current collector, and the negative electrode active layer can be collected as a test sample. Using a thermogravimetric analyzer (e.g., a TGA 550 thermogravimetric analyzer), the sample amount is 5mg-15mg. Under an air or oxygen atmosphere, the temperature is increased from room temperature (25℃) to 900℃ at a rate of 10℃ / min, and held at 900℃ for 40 minutes. This allows the non-silicon components in the negative electrode active layer to volatilize while the silicon is fully oxidized to silicon dioxide. Weigh the residual material. The silicon content in the negative electrode active layer can be obtained by the following formula: Silicon content in the negative electrode active layer = 7 × mass of residual material / (15 × mass of test sample). It should be noted that the test method for s is as follows: remove the adhesive tape from the battery, image the through-hole on the adhesive tape under an optical microscope, and mark a 1 mm mark on the image. 2 Within a given area, measure the diameter of each through-hole. For circular through-holes, directly measure their diameter and calculate the area of ​​a single through-hole (π×(d / 2)). 2 For non-circular through holes (e.g., hexagonal, polygonal, or irregular shapes), measure the circumcircle diameter of the through hole and calculate the area of ​​a single through hole (π×(d / 2)) based on the circumcircle diameter. 2 (where d is the circumcircle diameter). Summing the areas of all individual through holes yields the 1 mm value. 2 The total area s of the through-holes within the region. Repeat the measurement at least 3 different 1 mm measurements. 2 For the region, take the average value as the s value.

[0033] In one embodiment, the diameter of the through-hole 3 is d μm. When the through-hole 3 is circular, the diameter is the diameter of the circle. When the through-hole 3 is non-circular (e.g., elliptical, polygonal, or irregular), the diameter of the through-hole 3 refers to the diameter of the circumcircle of the through-hole 3, that is, the diameter of the smallest circle that can cover the through-hole 3. The diameter of the through-hole 3 reflects the opening size of a single through-hole 3, which directly affects the ability of the electrolyte to pass through the through-hole 3 and the structural integrity of the adhesive tape 2. The diameter d of the through-hole 3 and the mass content f% of ethyl fluoroacetate in the electrolyte satisfy the following condition: 0.5 ≤ d / f ≤ 10.

[0034] When the d / f ratio is less than 0.5, it means that the diameter of the through-hole 3 is too small relative to the content of ethyl fluoroacetate. An excessively small diameter of the through-hole 3 will create significant resistance to the passage of electrolyte, making it difficult for the electrolyte to smoothly enter the electrode assembly 1. The through-hole 3 has limited effect on improving wettability. Especially when the content of ethyl fluoroacetate is high, the electrolyte viscosity will increase again, and the flow properties will decrease. At this time, an excessively small diameter of the through-hole 3 will make it even more difficult for the electrolyte to pass through.

[0035] When the d / f ratio is greater than 10, it means that the diameter of the through-hole 3 is too large relative to the content of ethyl fluoroacetate. An excessively large diameter of the through-hole 3 will weaken the structural strength of the adhesive tape 2, reduce the maximum load-bearing capacity of the adhesive tape 2, and when the negative electrode expands during charging and discharging, the adhesive tape 2 is prone to breakage, loses its restraining effect on the electrode sheet, and thus leads to electrode sheet delamination and rapid capacity decay of the battery.

[0036] Therefore, by controlling d / f within the range of 0.5 to 10, the diameter of the through hole 3 can be matched with the viscosity characteristics of the electrolyte, so that the electrolyte can effectively enter the electrode assembly 1 through the through hole 3 while ensuring that the adhesive paper 2 has sufficient structural strength.

[0037] For example, d / f can be 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, 2.2, 2.5, 2.8, 3.0, 3.2, 3.5, 3.8, 4.0, 4.2, 4.5, 4.8, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, or a value within the range of any two of the above values. Further, in one embodiment, the diameter d of the through hole 3 satisfies: 10 μm ≤ d ≤ 50 μm. For example, the diameter d of the through hole 3 can be 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm, 50μm, etc., or a value within the range of any two of the above values.

[0038] It should be noted that the diameter d of the through hole 3 can be measured using an optical microscope. Specifically, remove the adhesive tape 2 from the battery, image the through hole 3 under an optical microscope, directly measure the diameter of a circular through hole 3, and measure the diameter of its circumscribed circle for a non-circular through hole 3. Measure the diameters of at least 10 through holes 3 and take the average value to obtain the d value. The d / f value is obtained by dividing the measured d (in micrometers) by the measured f (in percentage terms, e.g., 25 when f=25).

[0039] In one embodiment, the plurality of through holes 3 are arranged in an array, wherein the included angle formed by the lines connecting the centers of any three adjacent through holes 3 is 120°. That is, the lines connecting the centers of any one through hole 3 with the six nearest surrounding through holes 3 form six equal included angles, each of which is 120 degrees, thus forming a hexagonal honeycomb arrangement. This arrangement allows for a uniform distribution of the through holes 3, resulting in a more dispersed stress transmission on the adhesive tape 2, which helps to reduce local stress concentration and decrease the impact of the through holes 3 on the maximum load-bearing capacity of the adhesive tape 2.

[0040] In one embodiment, the through-hole 3 is at least one of circular, hexagonal, and polygonal shapes. Circular through-holes 3 have smoother edges and lower stress concentration. When hexagonal through-holes 3 are arranged in a honeycomb pattern, the spacing between adjacent through-holes 3 is more uniform, which is more conducive to the uniform distribution of stress.

[0041] In one embodiment, the distribution density of the through holes 3 is 100 to 500 per cm. 2 This allows for sufficient electrolyte channels while minimizing the weakening of the adhesive tape 2's structural strength by the through-holes 3. For example, the distribution density of the through-holes 3 can be 100 per cm³. 2 120 pieces / cm 2 150 pieces / cm 2 180 pieces / cm 2 200 pieces / cm 2 220 pieces / cm 2 250 pieces / cm 2 280 pieces / cm 2 300 pieces / cm 2 320 pieces / cm 2 350 pieces / cm 2 380 pieces / cm 2 400 pieces / cm 2 420 pieces / cm 2 450 pieces / cm 2 480 pieces / cm 2 500 pieces / cm 2 Values ​​equal to or within the range of any two of the above values.

[0042] In one embodiment, the distance between the centers of any two adjacent through holes 3 is between 0.1 mm and 5 mm. When the center-to-center distance between adjacent through holes 3 is less than 0.1 mm, the distance between the through holes 3 is too close, and the through holes 3 are easily connected, which greatly affects the structural integrity of the adhesive tape 2 and reduces the maximum load-bearing capacity of the adhesive tape 2 significantly. When the center-to-center distance between adjacent through holes 3 is greater than 5 mm, the distance between the through holes 3 is too far, the number of through holes 3 per unit area is small, the channels through holes 3 that the electrolyte can pass through are insufficient, and the improvement effect on wettability is relatively limited.

[0043] For example, the center-to-center distance between any two adjacent through holes 3 can be 0.1 mm, 0.2 mm, 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm, 3.0 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4.0 mm, 4.2 mm, 4.5 mm, 4.8 mm, 5.0 mm, etc., or a value within the range of any two of the above values.

[0044] In one embodiment, the thickness of the adhesive tape 2 is between 0.01 mm and 2 mm. When the thickness of the adhesive tape 2 is less than 0.01 mm, the structural strength of the adhesive tape 2 itself is low, making it difficult to be compatible with the adhesive application equipment, and it is also prone to breakage during battery use. When the thickness of the adhesive tape 2 is greater than 2 mm, the adhesive tape 2 occupies a large space, reducing the volumetric energy density of the battery.

[0045] For example, the thickness of the adhesive tape 2 can be 0.01 mm, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 2 mm, or a value within the range of any two of the above values.

[0046] It should be noted that the distribution density of the through holes 3 can be tested using an optical microscope. Specifically, the adhesive tape 2 is removed from the battery, and the through holes 3 on the adhesive tape 2 are imaged under an optical microscope. A 1 cm mark is drawn on the image. 2 In the area, count the number of through holes 3 in that area, and repeat the measurement at least 3 different 1 cm areas. 2The distribution density of through-holes 3 is obtained by averaging the values ​​over a given area. Select any two adjacent through-holes 3 and measure the distance between their centers. Repeat this measurement for at least 10 sets of adjacent through-holes 3, and average the results to obtain the distance between the centers of any two adjacent through-holes 3. The thickness of the adhesive tape 2 can be tested using a micrometer. Specifically, remove the adhesive tape 2 from the battery and use a micrometer to measure the thickness at at least 5 points at different locations on the adhesive tape 2. Average the results to obtain the thickness value of the adhesive tape 2.

[0047] In one embodiment, the silicon-based material includes silicon-carbon material, the cross-sectional profile of which has an interior angle greater than 180 degrees. That is, the particle shape of the silicon-carbon material is between that of spherical silicon-carbon and blocky silicon-carbon, and its surface has an inwardly concave region, the interior angle corresponding to which the concave region is an anomalous angle (i.e., an angle greater than 180 degrees).

[0048] This type of silicon-carbon material with a recessed structure can store electrolyte in its recessed areas, providing additional electrolyte reserves for the electrode interface during battery cycling. It also helps reduce localized stress concentration in the particles during charge and discharge, mitigating the damage to the particle structure caused by silicon volume expansion. Therefore, using this silicon-carbon material with a cross-sectional profile having an interior angle greater than 180 degrees can alleviate the expansion problem of high-silicon anodes to some extent, and by storing electrolyte in the recessed areas, it can further improve the wetting state of the electrode interface and reduce purple spots.

[0049] It should be noted that the interior angle mentioned in this application refers to the angle corresponding to the recessed portion formed on the cross-sectional profile of the silicon-carbon composite material particle. Specifically, in the scanning electron microscope cross-sectional image of the silicon-carbon composite material, taking the point on the cross-sectional profile of the silicon-carbon composite material particle that is closer to the center of the particle's cross-section as the starting point, two straight lines tangent to the cross-sectional profile of the particle are drawn. The interior angle formed between the two tangent lines with an angle greater than 180 degrees is the "first interior angle" mentioned in this application. Figure 4 As shown in the figure, A represents the first interior angle, and A1, A2, and A3 represent different first interior angles. The cross-sectional profile of the silicon-carbon composite material particles of this application includes one or more of the aforementioned first interior angles, and the region where the first interior angle is located corresponds to the groove-like recessed structure formed on the surface of the silicon-carbon composite material particles. This groove-like structure can increase the number of non-curved contact points on the surface of the silicon-carbon material, which helps to improve the contact between the particles and the electrolyte, as well as between the particles themselves; at the same time, this structure can reduce the sharp edges on the surface of the silicon-carbon composite material particles, which helps to reduce the risk of particle breakage due to local stress concentration during charge-discharge cycles.

[0050] In one embodiment, the electrolyte further includes a carbonate, such as at least one selected from ethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, and propylene carbonate. The carbonate content is e% based on the total mass of the electrolyte, satisfying 5 ≤ e ≤ 60%.

[0051] Carbonates play a role in dissociating lithium salts and reducing electrolyte viscosity in the electrolyte, thus helping to improve the ionic conductivity of the electrolyte. When the mass content of carbonates is less than 5%, the degree of lithium salt dissociation is low, the lithium-ion conductivity is low, and the electrolyte viscosity is high, which is not conducive to further improving the cycle performance of the battery.

[0052] When the mass content of carbonate is higher than 60%, carbonate will have a more obvious swelling effect on the adhesive layer of adhesive paper 2, weakening the fixing effect of adhesive paper 2 on the electrode sheet, which may cause adhesive paper 2 to fall off or decrease in adhesion during battery cycling.

[0053] Therefore, by controlling the mass content of carbonate within the range of 5% to 60%, it is possible to ensure that the electrolyte has good ionic conductivity while reducing excessive swelling of the adhesive layer of the adhesive paper 2 and maintaining the effective constraint of the adhesive paper 2 on the electrode.

[0054] For example, e% can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, etc., or a value within the range of any two of the above values.

[0055] It should be noted that the mass content of carbonates can be obtained by methods conventional in the art, such as gas chromatography (GC), gas chromatography-mass spectrometry (GCMS), or liquid chromatography (LC).

[0056] In one implementation, such as Figure 2 As shown, the distance between the two farthest through holes 3 along the first direction is L1. The first direction refers to the extension direction of the adhesive tape 2 from the first surface 11 of the electrode assembly 1 across the side to the second surface 12. L1 reflects the length of the distribution area of ​​the through holes 3 on the adhesive tape 2 along the first direction. The thickness of the electrode assembly 1 is L2, and L1 and L2 satisfy 50% ≤ L1 / L2 ≤ 90%.

[0057] When the ratio of L1 / L2 is less than 50%, the length of the distribution area of ​​the through hole 3 is too small relative to the thickness of the electrode assembly 1. The through hole 3 is mainly concentrated in a certain area in the thickness direction of the electrode assembly 1 and is not dispersed enough. It is difficult to obtain the wetting channel brought by the through hole 3 uniformly inside the electrode assembly 1, and the improvement effect of electrolyte wetting is not uniform enough.

[0058] When the ratio of L1 / L2 is greater than 90%, the length of the distribution area of ​​the through hole 3 is too close to the thickness of the electrode assembly 1. The through hole 3 is likely to extend to the corner of the adhesive tape 2 between the first surface 11 / second surface 12 and the side surface, or even extend to the first surface 11 / second surface 12. The adhesive tape 2 at the corner is subjected to more concentrated stress during battery use. If the through hole 3 is set in this area, it will further weaken the strength of the adhesive tape 2 at the corner, increase the risk of the adhesive tape 2 breaking at this position, and also be detrimental to the complete coverage of the first surface 11 and the second surface 12 by the adhesive tape 2.

[0059] Therefore, by controlling L1 / L2 within the range of 50% to 90%, the through holes 3 can be mainly distributed in the part of the adhesive tape 2 corresponding to the thickness direction of the electrode assembly 1, avoiding the through holes 3 from extending to the corner area. This provides sufficient wetting channels for the inside of the electrode assembly 1 while maintaining the integrity and constraint ability of the adhesive tape 2 in the stress concentration area.

[0060] For example, the ratio of L1 / L2 can be 50%, 55%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, or a value within the range of any two of the above values. Preferably, L1 is between 1.8 mm and 10 mm. For example, L1 can be 1.8 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, 8.5 mm, 9.0 mm, 9.5 mm, 10.0 mm, or a value within the range of any two of the above values.

[0061] It should be noted that L1 can be tested using an optical microscope. Specifically, the adhesive tape 2 is removed from the battery, and an image of the adhesive tape 2 is formed along a first direction under an optical microscope. The maximum distance between the edges of the two farthest through holes 3 in this direction is measured as L1. The thickness L2 of the electrode assembly 1 can be tested using vernier calipers. Specifically, after discharging the battery, the electrode assembly 1 is disassembled and removed. The thickness is measured at least 5 points at different locations along the thickness direction of the electrode assembly 1 using vernier calipers, and the average value is taken as L2.

[0062] In one embodiment, along a first direction, the adhesive tape 2 includes a first region 21, a second region 22, and a third region 23, with the second region 22 located between the first region 21 and the third region 23. The second region 22 has a through hole 3, while the first region 21 and the third region 23 do not. That is, the adhesive tape 2 is divided into three regions along the first direction, with a through hole 3 in the middle region and no through holes 3 in the regions on both sides. At least a portion of the first region 21 is located on the first surface 11 of the electrode assembly 1, and at least a portion of the third region 23 is located on the second surface 12 of the electrode assembly 1. Specifically, when the adhesive tape 2 is wrapped around the electrode assembly 1, the first region 21 of the adhesive tape 2 covers at least a portion of the first surface 11, and the third region 23 of the adhesive tape 2 covers at least a portion of the second surface 12.

[0063] Since the first region 21 and the third region 23 do not have through holes 3, these two regions can maintain the complete structure of the adhesive tape 2, which is beneficial for the adhesive tape 2 to adhere firmly to the first surface 11 and the second surface 12, and to provide complete coverage and protection for the first surface 11 and the second surface 12 of the electrode assembly 1. At the same time, the absence of through holes 3 in the first region 21 and the third region 23 also avoids the stress concentration and adhesive tape 2 breakage risk that may be caused by opening through holes 3 in the corner areas. The through holes 3 provided in the second region 22 provide a channel for the electrolyte to enter the interior of the electrode assembly 1. This three-segment regional division allows the through holes 3 to be mainly concentrated in the area of ​​the adhesive tape 2 corresponding to the side of the electrode assembly 1, while maintaining the integrity of the area where the adhesive tape 2 contacts the first surface 11 and the second surface 12, as well as the corner areas, thereby providing an electrolyte wetting channel while maintaining the effective constraint and protection of the electrode assembly 1 by the adhesive tape 2. In some embodiments, the length of the first region 21 along the first direction and the length of the third region 23 along the first direction may be equal or unequal.

[0064] In one embodiment, the positive electrode includes at least one first positive electrode and at least one second positive electrode. The first positive electrode includes a first positive current collector and a first positive active layer located on one side of the first positive current collector, i.e., the first positive electrode is a single-sided positive electrode. The second positive electrode includes a second positive current collector and second positive active layers located on both sides of the second positive current collector, i.e., the second positive electrode is a double-sided positive electrode. The first positive electrode is located on the outermost side of the electrode assembly 1, and the first positive active layer faces the center of the battery. That is, a first positive electrode is provided on each side of the electrode assembly 1 in the thickness direction, and the first positive active layers of both first positive electrode are facing the interior of the electrode assembly 1, while the other side of the first positive current collector (the side without an active layer) faces the exterior of the electrode assembly 1. This arrangement is suitable for stacked electrode assemblies 1, allowing the outermost first positive electrode to wrap around the inner second positive and negative electrodes, while the exposed side of the first positive current collector is in contact with the adhesive tape 2.

[0065] Because the outermost single-sided positive electrode of the stacked electrode assembly 1 has a positive active layer on only one side, the stress on both sides is different, making it more prone to outward flipping and squeezing the polypropylene layer of the aluminum-plastic film. Repeated squeezing will cause damage to the polypropylene layer, directly exposing the aluminum layer of the aluminum-plastic film and causing corrosion, ultimately leading to battery leakage and reliability issues. Furthermore, when the negative electrode contains a high content of silicon-based materials, the negative electrode contracts and expands significantly during charging and discharging. The repeated volume changes, combined with the unbalanced stress of the single-sided positive electrode, easily cause delamination between the single-sided positive and negative electrodes, resulting in the deactivation of the delaminated positive electrode, which in turn leads to a decrease in battery capacity and a shortened cycle life. Therefore, this application makes the following limitations on the adhesive tape 2 wrapping the stacked electrode assembly 1.

[0066] like Figure 3 As shown, the orthographic projection of the adhesive tape 2 onto the first surface 11 or the second surface 12 has a dimension W along the width direction X of 3 mm to 10 mm. The width direction X refers to the direction perpendicular to both the thickness direction and the height direction Y. This dimension reflects the width of the adhesive tape 2 covering the first surface 11 or the second surface 12. When this dimension is less than 3 mm, the bonding area between the adhesive tape 2 and the first surface 11 or the second surface 12 is small, and the adhesive tape 2 is prone to detaching from the electrode assembly 1, resulting in insufficient constraint on the electrode sheet. When this dimension is greater than 10 mm, the adhesive tape 2 will excessively cover the first surface 11 or the second surface 12, occupying too much surface area of ​​the electrode assembly 1, affecting the energy density and surface flatness of the battery.

[0067] For example, the size can be 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, etc., or a value within the range of any two of the above values.

[0068] like Figure 3 As shown, the dimension of the adhesive tape 2 projected onto the first surface 11 and the second surface 12 along the height direction Y is L3, and the dimension of the electrode assembly 1 along the height direction Y is H. L3 and H satisfy 0.3 ≤ L3 / H ≤ 0.9. When the ratio of L3 / H is less than 0.3, the dimension covered by the adhesive tape 2 along the height direction Y is too short, and the constraint effect of the adhesive tape 2 on the electrode assembly 1 may be insufficient. When the ratio of L3 / H is greater than 0.9, the length covered by the adhesive tape 2 along the height direction Y is too long, and the adhesive tape 2 almost covers the entire height of the electrode assembly 1, which is not conducive to the full wetting of the electrolyte. Therefore, by controlling L3 / H within the range of 0.3 to 0.9, sufficient space can be left for the electrolyte to penetrate from the side while maintaining the effective constraint of the adhesive tape 2 on the electrode assembly 1.

[0069] For example, L3 / H can be 0.30, 0.35, 0.40, 0.42, 0.45, 0.48, 0.50, 0.52, 0.55, 0.58, 0.60, 0.62, 0.65, 0.68, 0.70, 0.72, 0.75, 0.78, 0.80, 0.82, 0.85, 0.88, 0.90, or a value within the range of any two of the above values.

[0070] It should be noted that the dimensions of the adhesive tape 2 in each direction can be measured using vernier calipers. Specifically, after removing the adhesive tape 2 from the battery and flattening it, use vernier calipers to measure the width and height of the portion of the adhesive tape 2 covering the first surface 11 or the second surface 12. The dimension H of the electrode assembly 1 along the height direction Y can be measured using vernier calipers. After discharging the battery, disassemble and remove the electrode assembly 1, and measure its maximum dimension in the height direction Y.

[0071] In one embodiment, the first positive electrode sheet has multiple protrusions and multiple recesses opposite to the protrusions. A protrusion is a portion of the surface of the first positive electrode sheet that protrudes outwards, and a recess is a portion that is recessed inwards corresponding to the position of the protrusion. The protrusions and recesses can be formed by an embossing process, for example, by using a roller with an uneven surface to roll the first positive electrode sheet, forming a protrusion on one side of the first positive electrode sheet and a corresponding recess on the other side. The protruding direction of the protrusions is away from the center of the electrode assembly 1. That is, the first positive electrode sheet is located at the outermost edge of the electrode assembly 1, with the side not coated with the first positive active layer facing the outside of the electrode assembly 1, and the protrusions protrude outwards from this surface, i.e., the protrusions protrude towards the aluminum-plastic film.

[0072] This uneven structure can create local gaps between the first positive electrode and the separator, increasing the distance between them. This facilitates electrolyte penetration into the interface between the positive electrode and the separator, improving the wetting effect of the electrolyte on the interior of the electrode assembly 1. Simultaneously, the microspaces formed by the protrusions and concave portions can store a certain amount of electrolyte. During battery cycling, as the electrolyte is gradually consumed, the electrolyte stored in these microspaces can be released to replenish the electrolyte demand at the electrode interface, helping to extend the battery's cycle life.

[0073] In one embodiment, the height of the protrusion is from 3 μm to 60 μm, preferably from 5 μm to 30 μm. The height of the protrusion refers to the vertical distance from which the protrusion protrudes outward from the reference surface of the first positive electrode. By controlling the height of the protrusion within the range of 3 μm to 60 μm, an effective electrolyte channel and storage space can be formed between the first positive electrode and the separator.

[0074] For example, the height of the protrusion can be 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, etc., or a value within the range of any two of the above values.

[0075] The diameter of the circumcircle of the protrusion projected onto the first positive electrode sheet is 0.5 mm to 8 mm, preferably 1.5 mm to 4 mm. This allows for sufficient electrolyte storage space while minimizing the impact on the first positive electrode active layer. For example, the diameter of the circumcircle of the protrusion can be 0.5 mm, 0.8 mm, 1.0 mm, 1.2 mm, 1.5 mm, 1.8 mm, 2.0 mm, 2.2 mm, 2.5 mm, 2.8 mm, 3.0 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, 7.0 mm, 7.5 mm, 8.0 mm, or a value within any two of the above ranges.

[0076] It should be noted that the height and circumcircle diameter of the protrusion can be tested using an optical microscope or a laser confocal microscope. Specifically, the first positive electrode is removed from the battery, and the protrusion is imaged under a microscope. The vertical distance between the top of the protrusion and the reference surface of the first positive electrode is measured as the height, and the circumcircle diameter of the protrusion projected onto the first positive electrode is measured. For multiple protrusions, the height and circumcircle diameter of at least 10 protrusions are measured, and the average value is taken to obtain the corresponding parameter values.

[0077] The present application will be further described in detail below with reference to specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in this application. Where specific experimental steps or conditions are not specified in the embodiments and comparative examples, they can be performed according to the conventional experimental steps or conditions described in the literature in the art. Reagents or instruments used, unless otherwise specified, are all commercially available conventional reagent products.

[0078] It should be noted that, as a unit of measurement, part by mass refers to the mass proportion of a certain component in a mixture. For example, 1 part by mass can be 0.1g, 1g, 8g, 25g, 60g, 100g, or any other positive number.

[0079] Example 1 This embodiment provides a method for preparing a battery, including the following steps: Step 1: Preparation of the positive electrode sheet Preparation of the first positive electrode: Lithium cobalt oxide, a conductive agent (a mixture of single-walled and multi-walled carbon nanotubes), and polyvinylidene fluoride (PVDF) are placed in N-methylpyrrolidone (NMP) at a mass ratio of 98.50:0.8:0.7 and stirred evenly to obtain a positive electrode slurry; the above positive electrode slurry is uniformly coated on one side of the first positive electrode current collector, and after drying, rolling, and die-cutting, the first positive electrode is obtained; Preparation of the second positive electrode: Lithium cobalt oxide, conductive agent (a mixture of single-walled and multi-walled carbon nanotubes), and polyvinylidene fluoride (PVDF) are placed in N-methylpyrrolidone (NMP) at a mass ratio of 98.5:0.8:0.7 and stirred evenly to obtain a positive electrode slurry; the above positive electrode slurry is uniformly coated on both sides of the second positive electrode current collector, and after drying, rolling and die-cutting, the second positive electrode is obtained.

[0080] Step 2: Preparation of the negative electrode Based on the total mass of the negative electrode active layer, artificial graphite, silicon carbide material (commercially available, with multiple first interior angles, A1 being 252°, A2 256°, and A3 258°), polyacrylic acid, styrene-butadiene rubber, sodium carboxymethyl cellulose, and single-walled carbon nanotubes were mixed in a mass ratio of 64:32:1.1:2.1:0.3:0.5, and deionized water was added. The mixture was stirred under vacuum to obtain a negative electrode active slurry. This negative electrode active slurry was then uniformly coated onto both surfaces of the negative electrode current collector (copper foil). After drying, rolling, and slitting, the desired negative electrode sheet was obtained. The silicon content (a%) in the negative electrode active layer was 16%. The silicon content was controlled by adjusting the mass ratio of silicon carbide material to artificial graphite, and the total mass ratio of silicon carbide material to artificial graphite was 96%.

[0081] Step 3: Preparation of electrolyte In an argon-filled glove box (moisture < 1 ppm, oxygen < 1 ppm), ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate were mixed in a mass ratio of 30:40:30 to form a homogeneous organic solvent. Lithium hexafluorophosphate (18% by mass of the total electrolyte) and 2,2-difluoroethyl acetate (22% by mass of the total electrolyte) were slowly added and stirred until homogeneous to obtain the electrolyte. Based on the total mass of the electrolyte, the carbonate content (e%) was 60%.

[0082] Step 4: Preparation of the diaphragm An 8μm thick substrate is used, with a ceramic layer coated on one side of the substrate and an adhesive layer coated on the other side of both the ceramic layer and the substrate. The substrate is composed of PE, the ceramic layer includes alumina, and the adhesive layer is PVDF.

[0083] Step 5: Preparation of Adhesive Tape A 0.02 mm thick rubber adhesive film with a width of 15 mm was used. Through-holes with a diameter of 15 μm were fabricated on the adhesive film using a laser. The center-to-center distance between adjacent through-holes was 2.5 mm, and the through-hole density was 200 holes / cm². 2 Along the first direction, the distance L1 between the two farthest through holes is 4.0 mm, and they are centrally located.

[0084] Step 6: Assembly of the electrode assembly The first positive electrode sheet prepared above is rolled by a concave-convex roller to form a plurality of protrusions and a plurality of concave portions opposite to the protrusions on the surface of the first positive electrode sheet. The protrusions are from the side of the first positive electrode sheet with the positive electrode active layer to the empty foil area. The prepared first positive electrode, second positive electrode, negative electrode, and separator, with protrusions, are stacked in the following order to form an electrode assembly: the outermost electrode is the first positive electrode, and the positive active layer of the first positive electrode faces the center of the electrode assembly. The middle electrode is arranged in the following cycle: separator, negative electrode, second positive electrode, to obtain a bare cell. The bare cell is then soldered with tabs to obtain a stacked cell, i.e., an electrode assembly. The prepared adhesive tape is then attached to the electrode assembly, extending from the first side to the second side of the electrode assembly. The portion of the adhesive tape corresponding to the thickness direction of the electrode assembly has through holes, with the first area of ​​the adhesive tape located on the first side, the third area on the second side, and the second area located between the first and third areas and covering the side of the electrode assembly. The second area has through holes, while the first and third areas do not. The electrode assembly covered with adhesive tape is then placed in an aluminum-plastic film shell, sealed, and baked. The electrolyte prepared in the third step is injected under vacuum conditions, and then sealed again. Finally, the battery is produced through aging (45 °C for 6 hours), formation, and sorting processes. Among them, the orthographic projection of the adhesive tape on the first and second surfaces along the width direction is 5 mm, the orthographic projection of the adhesive tape on the first and second surfaces along the height direction is L3 63 mm, the orthographic projection of the electrode assembly along the height direction is H 87 mm, L3 / H=63 / 87≈0.72, the height of the protrusion is 20 μm, and the diameter of the circumcircle of the orthographic projection of the protrusion on the first positive electrode plate is 3 mm.

[0085] Comparative Example 1 The preparation method is basically the same as that in Example 1, except that no through holes are provided on the adhesive paper, that is, the adhesive paper is a complete rubber adhesive paper without any perforated structure.

[0086] Comparative Example 4 The preparation method is basically the same as that in Example 4, except that 2,2-difluoroethyl acetate is not included in the electrolyte.

[0087] The preparation methods of Examples 2-10, Comparative Examples 2-3, and Comparative Examples 5-6 are basically the same as those of Example 1. The differences are shown in Tables 1 and 2, where “ / ” indicates that the item does not exist.

[0088] Table 1 Table 2 Test case 1. Maximum load-bearing capacity test of adhesive tape The adhesive tape was cut into 10 cm long specimens and subjected to tensile testing using a universal testing machine. The test conditions were: tensile rate 10 mm / min, tensile load applied along the length of the specimen, and the maximum load value (in N) at which the specimen broke or failed was recorded. Three specimens were tested consecutively for each example or comparative example, and the arithmetic mean was taken as the maximum load-bearing capacity of that specimen.

[0089] 2. Observation and testing of lithium plating The batteries prepared in each embodiment and comparative example were charged to 4.5V using a constant current and constant voltage of 2C, with a cutoff current of 0.05C, and allowed to stand for 10 minutes. The batteries were then disassembled while fully charged, and the negative electrode was removed to observe whether metallic lithium was deposited on its surface.

[0090] The evaluation criteria for the degree of lithium plating are as follows: no visible lithium plating is recorded as "none"; sporadic, localized lithium plating in localized areas is recorded as "slight"; and continuous lithium plating over a large area is recorded as "severe". Five cells were tested for each example or comparative example.

[0091] 3. Cyclic performance test The batteries prepared in each embodiment and comparative example were charged to 4.5V at 25°C using a constant current and constant voltage of 1C, with a cutoff current of 0.05C. After resting for 10 minutes, they were discharged to 3.0V using a constant current of 0.5C, and the initial discharge capacity was recorded as C0. This charge-discharge cycle was repeated 500 times, and the discharge capacity after the 500th cycle was recorded as C0. 500 Cyclic capacity retention rate (%) = (C 500 / C0)×100%. Five cells were tested for each embodiment or comparative example, and the average value was taken.

[0092] The test results are shown in Table 3.

[0093] Table 3 Based on the test results in Tables 1 to 3, compared with Comparative Examples 1 to 6, the overall performance of each embodiment in suppressing lithium plating, improving the maximum load-bearing capacity of the adhesive paper, and the cycle capacity retention rate are significantly improved.

[0094] Although embodiments of the invention have been described in conjunction with the accompanying drawings, those skilled in the art can make various modifications and variations without departing from the spirit and scope of the invention, and such modifications and variations all fall within the scope defined by the appended claims.

Claims

1. A battery, characterized in that, It includes an electrode assembly (1) and an electrolyte. The electrode assembly (1) includes a positive electrode, a separator and a negative electrode stacked together. The electrode assembly (1) includes a first surface (11) and a second surface (12) disposed opposite to each other along its thickness direction. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side of the surface of the negative electrode current collector. The negative electrode active layer includes a silicon-based material, and the mass content of silicon element is a% based on the total mass of the negative electrode active layer. The electrode assembly (1) further includes adhesive tape (2), which extends from the first surface (11) to the second surface (12). The adhesive tape (2) has through holes (3) in the portion corresponding to the thickness direction of the electrode assembly (1). Within a unit square centimeter area of ​​the adhesive tape (2), the total area of ​​the through holes (3) is 5 mm. 2 The condition is satisfied that: 0.05 ≤ a × s ≤ 0.6; The electrolyte includes ethyl fluoroacetate, and the mass content of ethyl fluoroacetate is f% based on the total mass of the electrolyte, satisfying: 4≤f≤60%.

2. The battery according to claim 1, characterized in that, The diameter of the through hole (3) is d μm, which satisfies: 0.5≤d / f≤10; And / or, the mass content a% of the silicon element satisfies: 1≤a≤50.

3. The battery according to claim 2, characterized in that, The diameter d of the through hole (3) satisfies: 10≤d≤50; And / or, the through hole (3) is at least one of a circle, a hexagon, and a polygon; And / or, the distribution density of the through holes (3) is 100~500 per cm. 2 ; And / or, the distance between the centers of any two adjacent through holes (3) is 0.1 mm to 5 mm; And / or, the thickness of the adhesive tape (2) is 0.01 mm to 2 mm.

4. The battery according to claim 1, characterized in that, The silicon-based material includes silicon-carbon material, and the cross-sectional profile of the silicon-carbon material has an interior angle, the degree of which is greater than 180°.

5. The battery according to claim 1, characterized in that, The fluoroethyl acetate includes ethyl difluoroacetate; the ethyl difluoroacetate includes at least one of 2,2-difluoroethyl acetate and ethyl 2,2-difluoroacetate; preferably, the ethyl difluoroacetate includes 2,2-difluoroethyl acetate; And / or, the electrolyte further includes carbonate, and the mass content of the carbonate is e% based on the total mass of the electrolyte, satisfying: 5≤e≤60.

6. The battery according to claim 1, characterized in that, Along the first direction, the distance between the two farthest through holes (3) is L1, and the thickness of the electrode assembly (1) is L2, satisfying: 50%≤L1 / L2≤90%; Preferably, 1.8 mm ≤ L1 ≤ 10 mm.

7. The battery according to claim 6, characterized in that, Along the first direction, the adhesive tape (2) includes a first region (21), a second region (22) and a third region (23), the second region (22) being located between the first region (21) and the third region (23), the second region (22) having a through hole (3), the first region (21) and the third region (23) not having a through hole (3), at least a portion of the first region (21) being located on the first surface (11), and at least a portion of the third region (23) being located on the second surface (12).

8. The battery according to any one of claims 1 to 7, characterized in that, The positive electrode includes at least one first positive electrode and at least one second positive electrode. The first positive electrode includes a first positive current collector and a first positive active layer located on one side of the first positive current collector. The second positive electrode includes a second positive current collector and a second positive active layer located on both sides of the second positive current collector. The first positive electrode is located on the outermost side of the electrode assembly (1), and the first positive active layer faces the center of the battery. The orthographic projection of the adhesive tape (2) on the first surface (11) or the second surface (12) along the width direction (X) is 3 mm to 10 mm; and / or, the orthographic projection of the adhesive tape (2) on the first surface (11) or the second surface (12) along the height direction (Y) is L3, and the dimension of the electrode assembly (1) along the height direction is H, satisfying: 0.3≤L3 / H≤0.

9.

9. The battery according to claim 8, characterized in that, The first positive electrode has multiple protrusions and multiple recesses opposite to the protrusions, and the protrusion direction of the protrusions is away from the center of the electrode assembly (1).

10. The battery according to claim 9, characterized in that, The height of the protrusion is 3 μm to 60 μm; preferably, the height of the protrusion is 5 μm to 30 μm. And / or, the diameter of the circumcircle of the protrusion projected onto the first positive electrode sheet is 0.5 mm to 8 mm; preferably 1.5 mm to 4 mm.